(untitled) (Research, Society and Development, 2021)
Neurofibromas are uncommon benign tumors in the oral cavity, which are composed of Schwann cells, perineural-like cells, and fibroblasts. The diagnosis can be confirmed by histological examination and immunopositivity for the S-100 protein indicating its neural origin. Surgical excision is the treatment of choice, and the intraoral approach is the best route for a medium-sized lesion and the prognosis is excellent. This paper aims at to present a unusual case of large neurofibroma located at the cheek mucosa of a young man and review important aspects of this tumor in the oral cavity.